2021
DOI: 10.21203/rs.3.rs-923912/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accuracy Verification of 4D-CT Analysis of Knee Joint Movements: A Pilot Study Using a Knee Joint Model and Motion-capture System

Abstract: BackgroundFour-dimensional CT(4D-CT) is an advanced imaging method with the ability to acquire kinematic and three-dimensional morphological information. Although its use for analysis of the six degrees of freedom in the knee is expected, its accuracy has not been reported. This study aimed to use the optical motion-capture method to verify the accuracy of 4D-CT analysis of knee joint movement.MethodsOne static CT and three 4D-CT examinations of the knee joint model were obtained. The knee joint model was pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…A subject positioning protocol was used to ensure that the entire patella, and parts of the proximal tibia and the distal femur were continuously within the field of view during the scan. Prior validation studies have demonstrated that dynamic CT imaging is accurate ($1°and 1 mm of x,y,z rotation and translation) and comparable to other dynamic imaging techniques [9,10]. Given the high similarity in image acquisition, similar accuracies are expected in this study.…”
Section: Methodssupporting
confidence: 54%
“…A subject positioning protocol was used to ensure that the entire patella, and parts of the proximal tibia and the distal femur were continuously within the field of view during the scan. Prior validation studies have demonstrated that dynamic CT imaging is accurate ($1°and 1 mm of x,y,z rotation and translation) and comparable to other dynamic imaging techniques [9,10]. Given the high similarity in image acquisition, similar accuracies are expected in this study.…”
Section: Methodssupporting
confidence: 54%